U.S. STRATEGY IN CENTRAL ASIA: PROBLEMS AND ACHIEVEMENTS - YULDASHEVA, Guli (CENTRAL ASIA AND THE CAUCASUS, 2011)
The events of the last decades have again demonstrated the close interconnection among all the parts of the international relations system. The main masterminds of world development are now finding that they too are being drawn into the processes going on in vitally important geopolitical zones of the world far beyond their own borders.The Central Asia region is one of these zones for the following reasons:it is Geo strategically located at the intersection among many of the existing, potential, and planned transportation and pipeline routes;it has extremely rich natural and human resources;it is close in territorial-geographical, historical-cultural, and demographic terms to the hotbeds of instability in the Islamic world;most of the global challenges and threats (territorial, ethnonational, religious, environmental, and so on) are concentrated in its territory.